(untitled) (Architecture Image Studies, 2025)
This research aims to analyze the land acquisition conflict and find a balanced model for handling land acquisition conflicts for toll roads through a socio-legal approach to be the focus of this research design. The method in this research with analysis techniques for primary data is carried out using the Strauss and J Corbin type where data analysis has been carried out since the beginning when researchers are in the field. That is why researchers use interactive analysis by making field notes consisting of descriptions and reflections on data “. The results showed that the conflict over land acquisition for the section 1 toll road, package 1.1 of the Surakarta-Klaten section, was caused by differences in the calculation of compensation and differences of opinion regarding the value of compensation. This research also confirms that several cases show community objections to the results of the appraisal calculation. This is because many land and buildings are classified as agricultural land and therefore have a lower value. In addition, from the community perspective, land acquisition does not provide access to price negotiations for objects attached to the land, such as buildings, trees, wells, and small structures. This research also shows that another problem that becomes an obstacle in land acquisition for toll roads is the rejection of court decisions. As in the provisions of Law No. 2/2012 on Land Acquisition for Development for the Public Interest, after there is a decision that has permanent legal force, the compensation will be consigned (deposited) in the district court.